Merger to Attract Customer Interest: Case Study of Bank Syariah Indonesia (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
The aim of this research is to find out how the merger is implemented in attracting customer interest, to find out what the marketing strategy is BSI Denpasar Branch Office in attracting customer interest. Methodology The research used is qualitative research using triangulation in credibility testing as checking data from various sources in various ways and at various times. Informants in this research is an employee of Bank Syariah Indonesia Denpasar Branch and a BSI customer using purposive techniques. As well as data collection in the form of : Interviews and Documentation. These results show interest customers even with the merger.